Failure Modes in Servitization: A Process Theory - Sun, Xichen; Oliva, Rogelio (Journal of Operations Management, 2026)
ABSTRACT The implementation of servitization as a business strategy remains a significant challenge for firms seeking to offer integrated product‐service bundles. Despite the growing body of research in the servitization literature, an integrative framework for explaining the recurring failures in servitization efforts has yet to emerge. Through a qualitative meta‐analysis of empirical evidence documented in existing case studies, we develop a process theory that examines the tensions between product and service businesses during the service business development process. Our study identifies three common servitization failure modes, highlights the contributing factors across various stages of servitization, and establishes causal links between structural elements and behavioral outcomes to explain the heterogeneity in service business performance. By adopting a process perspective, we provide a more nuanced understanding of servitization dynamics, offering new insights that complement and extend established theories on firm growth and capability development. We conclude by discussing managerial implications for firms pursuing a servitization strategy and outlining future research steps to test and further refine the proposed theory.